2016
DOI: 10.21315/jcdc2016.21.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Special Purpose Vehicle Organisation Skill Sets Taxonomy for Effective Public-Private Partnership Infrastructure Project Delivery

Abstract: (2016). Evaluation of special purpose vehicle organisation skill sets taxonomy for effective public-private partnership infrastructure project delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In terms of forming the SPV, Ahadzi and Bowles (2004) found that the SPV viewed the previous experience of its partners in delivering projects as very important. SPV partners are normally selected based on the expertise that they bring to the consortium (Siering et al 2013), with expertise in risk management being particularly important (Gomez and Gambo 2016). Carpintero (2015) found that large international Spanish SPVs operating in Canada tended to have innovative construction and design practices in PPPs, strong financial expertise and access to finance due to pre-established relationships with financiers from previous projects.…”
Section: Figure 1 Above Frommentioning
confidence: 99%
“…In terms of forming the SPV, Ahadzi and Bowles (2004) found that the SPV viewed the previous experience of its partners in delivering projects as very important. SPV partners are normally selected based on the expertise that they bring to the consortium (Siering et al 2013), with expertise in risk management being particularly important (Gomez and Gambo 2016). Carpintero (2015) found that large international Spanish SPVs operating in Canada tended to have innovative construction and design practices in PPPs, strong financial expertise and access to finance due to pre-established relationships with financiers from previous projects.…”
Section: Figure 1 Above Frommentioning
confidence: 99%
“…When it comes to economic potential, Russia can compete with countries such as Germany and France and surpasses China and the United States in terms of territory, but the degree of realization of economic potential in Russia is much lower than in the abovementioned states (Gomez and Gambo 2016). However, the intra-systemic indicators of military-economic security are not encouraging; the military-industrial complex exists mainly on export orders, supplies to the security forces are insignificant and their weapons and military equipment have not been updated since the "collapse conversion".…”
Section: The Significance Of the Russian Defence Industry Complex And The Development Of Its Innovation Potentialmentioning
confidence: 99%
“…Before thinking of referring specific health project to implementation using the partnership contract, there must be a total review for government's ability to finance, administration, service quality and compared with those in the private sector [18]. After that, the first step requires determining and understanding the main issues and problems related to the needs of the ministry (or the local government, related to the health) in hospital management services in a chosen site or area.…”
Section: Analysis Of Needmentioning
confidence: 99%